Policies Supporting The Export Capability Of Small And Medium-Sized Enterprises In Dong Nai Province - Tam, Phan Thanh (Social Science Learning Education Journal, 2017)
Small-and medium-sized enterprises (SMEs)in Vietnam had stated their role in the countrys economy by contributing more than 40 percent to the gross domestic product (GDP), while attracting more than 50 percent of the total laborers. All supporting policies for small-and medium-sized enterprises, which account for more than 95 percent of the total Vietnamese enterprises, they should be included under one law.The studyresults showed that there were 200 managers of SMEs in Dong Nai province whointerviewed and answered about 19 questions. Data collected from July 2016 to December 2016forSMEs in Dong Nai province.The paper had been analyzed KMO test, Cronbachs Alpha and the result of KMO analysis which used for multiple regression analysis. Managersâ responses measured through an adapted questionnaire on a 5-point Likert scale (Conventions: 1: Completely disagree, 2: Disagree, 3: Normal; 4: Agree; 5: completely agree). Hard copy and online questionnaire distributed among 10.000 managers of SMEs in Dong Nai province. In addition,the exploratory factor analysis (EFA) results showed that there were five factors, which included of factors following Human resources (X1), Marketing (X2), Leadership (X3), Technology (X4) and Product (X5) with significance level 5 percent. In addition, all of five components affecting the export capability of small and medium-sized enterprises in Dong Nai provincewith significance level 5 percent. The research results processed from SPSS 20.0 software.